Longman dictionary of contemporary english : The living dictionary (Longman, 2003)
Longman Dictionary of Contemporary English is a comprehensive learner's dictionary designed for intermediate to advanced English users. It provides clear definitions using a limited defining vocabulary, real-life example sentences, collocations, grammar notes, and usage tips. The dictionary is especially useful for improving vocabulary, writing, and speaking skills in academic and everyday contexts.